Expedition of Torrens system in the common law world and its Asian development in Singapore and Hong Kong - Wu, Richard; Zul Kepli, Mohd Yazid (Thompson Reuters, 2012)
In the common law world, Australia was the first country to adopt, in the 19th century, a title registration system, widely known as the Torrens system. The system become popular in many common law countries. In Asia, countries such as Malaysia and Singapore adopted the system. In this article, the authors cinsider the global implementation of title registration systems, focusing on common law countries such as Australia, England and the United States. They also analyse the development of title registration systems in two Asian cities, namely Singapore and Hong Kong. They argue that Hong Kong can learn three lessons from Singapore for its title registration reform.